Intraocular pressure during corneal flap preparation: comparison among four femtosecond lasers in porcine eyes - Vetter, Jan Markus; Holzer, Mike P.; Teping, Christian; Weingärtner, Wolf E.; Gericke, Adrian; Stoffelns, Bernhard; Pfeiffer, Norbert; Sekundo, Walter (Journal of refractive surgery, 2011)
Purpose:To compare the course of intraocular pressure (IOP) during corneal flap preparation - using four different femtosecond lasers in porcine globes. - Methods:Forty-eight (12 in each group) enucleated globes were successfully cannulated through - the optic ...
Erstmals am 10. Dezember 2010 online veröffentlicht
Gesehen am 08.12.2022